Regenerating island-derived protein 3E concentrations in healthy dogs and dogs with various inflammatory processes - Laureen M. Peters; Theresia Reding Graf; Rolf Graf; Meike Mevissen; Judith Howard (PLoS ONE, 2025)
Background Blood concentrations of regenerating island-derived proteins (REG) are high in humans with sepsis, acute pancreatitis, and gastrointestinal diseases. REG3E was recently identified in canine pancreas and blood, but concentrations in dogs with various diseases are unknown. Objectives To measure and compare REG3E concentrations in dogs with sepsis, acute pancreatitis, gastrointestinal diseases, and healthy dogs. Methods Cross-sectional study measuring plasma REG3E concentrations using an in-house developed ELISA in stored convenience samples from client-owned dogs with naturally occurring sepsis (n = 44), acute pancreatitis (n = 42), acute (n = 25) and chronic gastrointestinal diseases (n = 23), and healthy controls (n = 80). Concentrations of REG3E are compared among groups and between survivors and non-survivors to discharge using the Kruskal-Wallis test with post-hoc Conover analysis and independent samples t-tests. Results REG3E concentrations differed significantly among all groups (P < 0.005), except between sepsis and acute pancreatitis (P = 0.936). Median concentrations (interquartile range [ng/mL]) were 36.5 (30–89) in healthy dogs, 200 (103.5–361.5) in dogs with chronic gastrointestinal diseases, 634 (257–1060) in dogs with acute gastrointestinal diseases, 1644.5 (710 − 4122) in dogs with acute pancreatitis, and 1736 (480.5–3416) in septic dogs. Non-survivors (n = 33) had significantly higher REG3E concentrations than survivors when compared across all clinically ill dogs (P < 0.001) and within the sepsis group (n = 20; P = 0.0133), but not within the acute pancreatitis group (n = 13; P = 0.248). Conclusions and clinical importance Plasma REG3E concentrations are higher in dogs of all disease categories, particularly in dogs with sepsis and acute pancreatitis, but with considerable overlap between different diseases. High REG3E concentrations may be associated with poor prognosis in septic dogs. Thus, REG3E is likely to reflect inflammation and merits further investigations to refine its potential as a diagnostic and decision-making biomarker in this species.